HOW FOOD CONSUMPTION PATTERN AND DIETARY DIVERSITY DESCRIBE FOOD SECURITY: EVIDENCE FROM YOGYAKARTA AND EAST NUSA TENGGARA - Nur Firdaus; Bintang Dwitya Cahyono (Jurnal Ekonomi dan Pembangunan, 2025)
According to Food Security Agency, food consumption pattern should meet nutrition standards and follow desirable dietary pattern (Pola Pangan Harapan/PPH). PPH is an indicator for nutritional dietary intake. This study aims to analyse food consumption pattern and dietary diversity in Yogyakarta and East Nusa Tenggara; and how they influence food security. The household data survey (Susenas) 2014 showed that PPH scores for Yogyakarta is higher than East Nusa Tenggara. From these scores, Yogyakarta has better food consumption pattern and led to diverse food intake. In Yogyakarta, people have been diversifying their consumption in accordance with the concept of PPH. This means that people have realised to meet their nutrition by consuming nutritious food and help them not only to achieve food security but also nutrition security. Moreover, people have used local-based food to be consumed so that they do not depend on their current food. Meanwhile, in East Nusa Tenggara, people tend to meet their needs regardless their food has good nutrition or not. In addition, dietary diversity or PPH is influenced by some factors, such as education, family size, age of the household head, and expenditure. These results confirm that diverse consumption pattern showed high food security and those factors should be concerned to improve the quality of food consumption.